Effects of the COVID-19 pandemic on emotional and behavioral problems and sleep problems in adolescents - Medise, Bernie Endyarni; Reza, Maulana Okta; Devaera, Yoga; Soebadi, Amanda; Chozie, Novie Amelia; Pudjiadi, Antonius H (Indonesian Pediatric Society, 2023)
Background The asynchrony rapid phase of cognitive, physical and emotional development occurring in adolescence may result in various issues such as risk-taking behavior, psychosocial and emotional problems. School closure during the COVID-19 pandemic has caused a tremendous change in adolescent lifestyle and habits, including sleep patterns. causing added challenges to adolescents’ emotional and behavioral problems. Objective To identify the association between sleep disorders with emotional and behavioral problems during the COVID-19 pandemic in urban and rural adolescents. Methods We conducted a cross-sectional study among adolescents aged 12-18 years from November to December 2021 in two provinces, DKI Jakarta and Riau Islands. We recruited students consecutively from randomly selected junior and senior high schools. We used the Strengths and Difficulties Questionnaire (SDQ) and the Pittsburgh Sleep Quality Index (PSQI) to screen for emotional and behavioral problems and for sleep disorders, respectively. The questionnaires were sent electronically to each subject after obtaining parental consent. Results There were 400 subjects included in our study, of which 64% were female. The prevalences of COVID-19 amongst subjects in urban and rural areas were COVID-19 12.5% and 5.5%, respectively. Emotional and behavioral disorders as well as sleep disorders were more common in rural than urban areas (13 vs. 11.5% and 50.5% vs. 38%; P=0.012, respectively). Sleep disorders were associated with the SDQ subscales of emotional symptoms [PR 4.88 (95%CI 2.97 to 8.03); P<0.01), conduct problems [PR 3.71 (95%CI 1.53 to 9.04); P=0.02), hyperactivity/inattention [PR 6.05 (95%CI 2.58 to 16.17); P<0.01], and peer relationship problems [PR 3.28 (95%CI 1.33 to 8.09); P<0.01). Conclusion Sleep disorders among adolescents during COVID-19 pandemic were associated with emotional and behavioral problems. Adolescents who live in rural areas were more likely to have sleep disorders, emotional and behavioral problems.